INTRODUCTION TO INDUSTRY-BASED ENTREPRENEURSHIP PROGRAMSCREATIVE FOR ORPHANAGE STUDENTS SUSTERAN ALMA SIMALUNGUN - Ben Setiawan; Doortua; Ibnu Fajar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Entrepreneurship also creates and provides products that can be more valuable and useful to meet the needs and desires of society.Creativity and innovation are important elements in entrepreneurship.Over the past few years, entrepreneurship has become one of the topics discussed in the learning process of students at various levels, both at the primary, secondary, and tertiary education levels.Awareness to develop creativity and innovation from a young age has increased. Basically every child is born with creative potential. Therefore, children need to be guided and directed to develop their creative potential optimally.entrepreneurial activities that have been carried out by studentsJUNIOR HIGH SCHOOLAlma Simalungun Orphanageis market day. But so far, these activities have only been in the form of buying and selling activities within the school environment. Therefore, the Orphanage of the Sisters of Alma Simalungun also sees the importance of introducing the business world for students, considering that so far the students still do not really understand the essence of entrepreneurial activities.